1996
DOI: 10.1021/ie950702a
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Mesoporous Molecular Sieve MCM-41

Abstract: The discovery of mesoporous molecular sieves, MCM-41, which possesses a regular hexagonal array of uniform pore openings, aroused a worldwide resurgence in this field. This is not only because it has brought about a series of novel mesoporous materials with various compositions which may find applications in catalysis, adsorption, and guest-host chemistry, but also it has opened a new avenue for creating zeotype materials. This paper presents a comprehensive overview of recent advances in the field of MCM-41. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
374
0
13

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(391 citation statements)
references
References 93 publications
4
374
0
13
Order By: Relevance
“…These materials have perfectly long-range order, highly tunable pore size and good surface characteristics which make them an ideal material for various applications [5][6][7]. The polymer or reactive groups in the nano-sized pores extending along the channels to the openings will not only enhance the miscibility through the entanglement and inter-diffusion between the matrix and the particulate, but also highly suppress the aggregation of fillers.…”
Section: Introductionmentioning
confidence: 99%
“…These materials have perfectly long-range order, highly tunable pore size and good surface characteristics which make them an ideal material for various applications [5][6][7]. The polymer or reactive groups in the nano-sized pores extending along the channels to the openings will not only enhance the miscibility through the entanglement and inter-diffusion between the matrix and the particulate, but also highly suppress the aggregation of fillers.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactant-templated mesoporous materials have some specific features such as high surface areas and high adsorption capacities including the uniformity and periodicity of tunable mesopores [9][10][11], which are widely applicable to adsorbents and catalytic supports [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been studied as catalysts, support and sorbents. [13][14][15][16] In our previous study, platinum doped MCM-41 catalyst showed higher specific activity than Pt/Al 2 O 3 for the SCR reaction. 9 The present study concentrations as that used in the activity measurements, i.e., 1000 ppm NO (when used), 1000 ppm C 3 H 6 (when used), 2% O 2 (when used) and balance of He.…”
Section: Introductionmentioning
confidence: 89%